Metabolic Wellbeing and Covid-19 - Carmine Finelli (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2020)
The effects of infection with SARS-CoV-2 on host health are complex and major differences in the severity of the disease are observed. The best choices, nevertheless, are prevention and management. The main functions of genomic metabolic processes regulated by various physiological mechanisms are defined by the metabolic health of a person. Disordered genomic metabolic processes and a reduction in metabolic health are triggered by disruption of these mechanisms. Weaknesses health is the main risk factor for extreme COVID-19. It is probable that potential physiological changes induced by metabolic syndrome and T2D will overcap with COVID-19, potentially exacerbating the course of the disease. Although chronic diabetes hyperglycaemia contributes to harm that can exacerbate the path of the disease in COVID-19, recent research indicates that in patients with COVID-19 and T2D, dysregulated glucose by itself is counterproductive. To regulate the host inflammatory response, to reduce tissue susceptibility to inflammatory damage signals and to maintain physiological function during the extreme and critical phase of infection, glycaemic control is essential.